Exploring the role of voluntary local and national reviews in advancing knowledge of education-related SDGs in TVET: A comparative case study of Pittsburgh and Nairobi - Matu, Jeffrey; Brennan, Mark A. (Nordic Journal of Comparative and International Education (NJCIE), 2025)
This study investigates how global Sustainable Development Goals (SDGs) are adapted within Technical and Vocational Education and Training (TVET) systems by examining two institutions with distinct governance frameworks: the Community College of Allegheny County (CCAC) in the U.S. and Kabete National Polytechnic in Kenya. While previous research examines SDG integration broadly, this study addresses a critical gap by analyzing how governance structures, whether participatory or centralized, shape SDGs implementation within TVET institutions. Using qualitative methods and applying Critical Discourse Analysis to 19 interviews and a survey of 75 students, this study reveals that CCAC’s decentralized and stakeholder-driven governance fosters institutional and organizational learning by allowing flexible adaptation and responsive SDG alignment. In contrast, Kabete’s top-down and policy-driven governance ensures national consistency but limits institutional autonomy, hindering localized innovation. These findings highlight that governance structures play a pivotal role in determining the effectiveness of SDG integration in TVET, influencing how institutions adapt policies, engage stakeholders, and implement sustainability education. The study emphasizes the need for governance frameworks that are both adaptable and contextually relevant, balancing national oversight with institutional flexibility. By providing comparative insights, this research offers practical recommendations for policymakers and educators, advocating for governance reforms that enhance SDG implementation in TVET systems worldwide.